KAPASITAS ADSORPSI METILEN BIRU OLEH LEMPUNG CENGAR TERAKTIVASI ASAM SULFAT - Alhusnalia Ramadhani; Muhdarina '; Amilia Linggawati (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
> Cengar clay activated sulfuric acid (LCA) was a residual solids synthesized liquid coagulant. LCA was obtained after calcination process at 700°C for 3 hours and activated with sulfuric acid 0.2; 0.4 and 0.6 mol. LCA has been used as an adsorbent for the adsorption of methylene blue dye aqueous solution. Methylene blue adsorption capacity was determined by the effect of stirring time and the concentration of the adsorbate. Through the Langmuir isotherm models it was obtained that the maximum adsorption capacity of methylene blue by LCA0,2; LCA0,4 and LCA0,6 was 2,0214 mg/g; 3,3955 mg/g and 3,8402 mg/g respectively with stirring time of 10 minutes and the optimum concentration 40 ppm. This LCA actually be able to remove methylene blue by 50.51% (LCA0,2); 53.53% (LCA0,4) and 77.74% (LCA0,6).